Water point mapping in Tanzania :making the voices of data collectors audible - Georgiadou, Yola (RWSN, 2020)
Any attempt to develop mobile-phone based platforms that allow citizens themselves to report data on near-by rural water points and update the Water Point Mapping System (WPMS) baseline in Tanzania depends on an understanding of reporting practices of water users or their representatives within the local context. The aim of this paper is to describe such reporting practices to official data collectors during the nation-wide baseline data collection for the WPMS project (May 2011 to April 2013). We draw on fieldwork for a five-year action research project (2012-2017) titled Sensors, Empowerment and Accountability in Tanzania (SEMA), and funded by NWO-WOTRO Science for Global Development. Our conclusion is that working with the grain of actual information flows between local institutions may be a clumsy solution to rural water services, but it makes elegant failures less probable.